A multi-centred randomised trial of radical surgery versus adjuvant chemoradiotherapy after local excision for early rectal cancer. Issue 1 (December 2016) - Borstlap, W.; Tanis, P.; Koedam, T.; Marijnen, C.; Cunningham, C.; Dekker, E.; van Leerdam, M.; Meijer, G.; van Grieken, N.; Nagtegaal, I.; Punt, C.; Dijkgraaf, M.; et al.
Abstract Background Rectal cancer surgery is accompanied with high morbidity and poor long term functional outcome. Screening programs have shown a shift towards more early staged cancers. Patients with early rectal cancer can potentially benefit significantly from rectal preserving therapy. For the earliest stage cancers, local excision is sufficient when the risk of lymph node disease and subsequent recurrence is below 5 %. However, the majority of early cancers are associated with an intermediate risk of lymph node involvement (5–20 %) suggesting that local excision alone is not sufficient, while completion radical surgery, which is currently standard of care, could be a substantial overtreatment for this group of patients. Methods/Study design In this multicentre randomised trial, patients with an intermediate risk T1-2 rectal cancer, that has been locally excised using an endoluminal technique, will be randomized between adjuvant chemo-radiotherapylimited to the mesorectum and standard completion total mesorectal excision (TME). To strictly monitor the risk of locoregional recurrence in the experimental arm and enable early salvage surgery, there will be additional follow up with frequent MRI and endoscopy. The primary outcome of the study is three-year local recurrence rate. Secondary outcomes are morbidity, disease free and overall survival, stoma rate, functional outcomes, health related quality of life and costs. The design is a non inferiority study with a total sample size of 302 patients. Discussion The results of the TESAR trial will potentially demonstrate that adjuvant chemoradiotherapy is an oncological safe treatment option in patients who are confronted with the difficult clinical dilemma of a radically removed intermediate risk early rectal cancer by polypectomy or transanal surgery that is conventionally treated with subsequent radical surgery. Preserving the rectum using adjuvant radiotherapy is expected to significantly improve morbidity, function and quality of life if compared to completion TME surgery. Trial registration NCT02371304, registration date: February 2015